American Cosmic: UFOs, Religion, Technology, by D.W. Pasulka. - Rapport, Jeremy (International journal for the study of new religions, 2020)
American Cosmic: UFOs, Religion, Technology, by D.W. Pasulka. 2019, Oxford University Press. Hb. $24.95. ISBN-13: 9780190692889.